Poema e poesia através da literatura infantil - SANTOS, Josiane Cardoso dos (2019)
The work with children's literature has the possibility of developing the formation of competent readers / writers, since the development of children's imagination is stimulated, making the subject someone critical and involved with the act of interpretation of the world, and through this understanding can modify the context in which it is inserted; the aim of this work is to show the importance as well as the differences between the poem and poetry in children's literature, exposing the conceptions of scholars about poetry and poem, reflecting on the importance of poetic language as well as its structure. It is justified the mediation of the poetic text as a factor of paramount importance for the child's imagination, so it is necessary to present examples and analyzes of poems written for the children's public with themes linked to their daily life making use of an accessible language learning.